Bobath method in the physiotherapeutic treatment of children with Down Syndrome: systematic review (Research, Society and Development, 2021)
Down Syndrome (DS) is a congenital disorder caused by trisomy of chromosome 21, which triggers deficits in motor coordination, muscle hypotonia and hyperflexibility. A child with Down Syndrome has a delay in motor development, which makes it difficult to produce and control physical and daily activities. The Bobath Method can be treated, with deficit of movements, functions and postural control, caused by an injury to the Central Nervous System. People with Down's Syndrome have phenotypic developmental characteristics that arise since birth, such as muscle hypotonia, the first characteristic evidenced at birth. A search will be made for the articles available on the Scielo platform, using the descriptors Down syndrome, child, physiotherapy, as well as their combinations and variations in the database. The research will be carried out by two independent researchers. Inclusion criteria: articles in Portuguese and English of the article in case studies and published in the last 10 years excluded from articles that did not provide the full text, cohort studies.